Oxidation of benzyl alcohol to benzaldehyde by tert-butyl hydroperoxide over nanogold supported on TiO2 and other transition and rare-earth metal oxides - Choudhary, Vasant R.; Dumbre, Deepa K.; Bhargava, Suresh Kumar (Industrial & Engineering Chemistry Research, 2009)
Liquid-phase oxidation of benzyl alcohol to benzaldehyde by tertiary butyl hydroperoxide (at 95 degrees C) over nanogold supported oil TiO2 and other transition-metal oxides (viz, MnO2, Fe2O3, CoOx, NiO, CuO, ZnO, and ZrO2) or rare-earth oxides (viz, La2O3, Sm2O3, Eu2O3, and Yb2O3) by the homogeneous deposition-precipitation (HDP) method has been investigated. The Au/TiO2 catalyst, prepared using the HDP method, showed high activity and selectivity in the reaction. The ZrO2-Supported nanogold catalyst (HDP) also showed very good performance. The Au/TiO2 catalyst that was prepared using the deposition-precipitation (DP) method, however, showed poor catalytic activity, mostly because of its much-lower gold loading and/or lower Au3+/Au-0 ratio. Irrespective of the catalyst preparation method, the catalytic activity increased as the gold loading increased. The gold deposition method strongly influenced the amount of gold that was deposited on TiO2, the gold particle size distribution, and also the surface Au3+/Au-0 ratio; using the HDP method, the gold deposition was much larger, the gold particle size was smaller, the gold particle size distribution was much narrower, and the Au3+/Au-0 ratio was higher. Both the metallic and ionic gold species (Au-0 and Au3+) are present in the Au/TiO2 catalyst. However, the Au3+ species are mostly responsible for the high catalytic activity in the oxidation process.